ANGOCIN Anti-Infekt N in the treatment of urinary and respiratory tract infections: A pharmacy-based non-interventional observational study - Elisabeth Gabor; Nina Kassner; Meinolf Wonnemann; Yvonne Ziegler (Phytomedicine Plus)
Background: Several studies have verified the efficacy and safety of a nasturtium and horseradish combination (ANGOCIN Anti-Infekt N, further referenced as ANGOCIN) for the treatment of acute respiratory and urinary tract infections. Study design and purpose: This was a prospective pharmacy-based non-interventional cohort study to gain further insights into the use of ANGOCIN to treat respiratory (RTI) and urinary tract infections (UTI) under real-world conditions using a web-based patient survey (electronic patient reported outcome (ePRO)). Methods: Participants were asked to register and take part in a patient survey when they purchased ANGOCIN at a German pharmacy. They were asked to answer the survey questions over a 14-day period. Results: Participants (N = 479, mean age 41.5 ± 13.8 years) reported significant improvement of symptoms and subjective well-being under ANGOCIN treatment. For most participants (>60 %), the first symptom improvement occurred within the first two days of therapy, and the time to complete or sufficient symptom improvement was 12 days. This corresponds directly to the respective median duration of ANGOCIN intake (12 Days for RTI, 11 Days for UTI). Furthermore, almost all participants (96.5 %) were satisfied or even better with ANGOCIN treatment. Most of the participants (90.2 %) did not require additional antibiotics to treat their acute infection. The main reason for study discontinuation was the feeling of regaining health after ANGOCIN therapy (60 %); only a few participants terminated ANGOCIN therapy due to low tolerability (1.2 %). Most of the participants (96.5 %) stated that they intend to use ANGOCIN again for the next RTI or UTI, respectively. Conclusions: These results are in line with results from other studies that herbal medications contribute to the recovery of infections. Furthermore, they reflect the S3-guideline statement that symptom-reducing herbal medications are a good alternative to antibiotics in treating uncomplicated acute and recurrent UTI. ANGOCIN is an effective and well-tolerated self-medication for RTI and UTI.